Improving the Degree of Health in the Elderly Through Health Checks and Education - Rachmawaty M. Noer; Aprina Damaiana Silalahi; Dini Mulyasari; Novika Sari; Ermawaty Ermawaty; Faizal Triharyadi; Dewi Tampubolon; Bevoor Bevoor (Pengabdian: Jurnal Abdimas, 2023)
Background. The thesis focuses on the elderly as the final stage of human development and acknowledges that individuals in old age undergo various changes. The research is conducted at the Nuriah Nursing Home, located in Kecamatan Sei Lakam, Kabupaten Karimun. The purpose of the research is to identify the main health problems faced by the elderly in the nursing home, specifically the risk of declining health status. The thesis mentions specific health problems prevalent among the elderly, such as chronic kidney disease (CKD), high blood pressure, heart disease, rheumatism, paralysis, and diabetes mellitus. Purpose. This activity aims to determine the health status. Method. The method used is by conducting health checks and counseling followed by 5 elderly people.. Results. The results of this activity showed that from 5 elderly people, 1 elderly had hypertension because the elderly underwent dialysis 2 times a week. 1 elderly suffers from malnutrition. 1 elderly had dementia, and one elderly experienced long bed rest. Conclusion. . The conclusion is that 70% are all carried out / assisted by orphanage officers. Starting from bathing, clothes, chapters, and tubs. The elderly seem to understand how to improve their health status. instructional approaches to meet the specific needs of their students.